Non-uptake of childhood vaccination among the children of HIV-infected mothers in sub-Saharan Africa: A multilevel analysis - Olatunji O. Adetokunboh; Olalekan A. Uthman; Charles S. Wiysonge (Taylor & Francis Group, 2018)
The aim of this study was to develop and test models for non-uptake of three doses of diphtheria-tetanus-pertussis containing vaccines (DTP3) among children of women living with HIV in sub-Saharan Africa. The study used demographic and health survey data from 27 sub-Saharan African countries that have the required HIV and immunization data sets. Multivariable logistic regression models were used to assess the relationship between individual and contextual factors associated with non-uptake of DTP3 among the children. At the individual level, the odds of non-uptake of DTP3 decreased with formal education, increasing age and access to media. The full model shows that the odds of non-uptake of DTP3 is increased among unemployed women, those living in communities with high illiteracy rate and in countries with low adult literacy level. For a child who moved to another country or community with a higher probability of DTP3 non-uptake, the median increase for the odds of DTP3 non-uptake would be 2.24% and 1.22% respectively for country and community. This study shows that individual and contextual factors contributed significantly to non-uptake of DTP3 among the children of women living with HIV. Interventions should be focused on women living with HIV who are young mothers, unemployed women, those without formal education, individuals living in communities with high illiteracy rate and in countries with low adult literacy rate. The use of mass media tools and creation of more employment opportunities for HIV-infected women could improve vaccination coverage among their children.